The Geography of Scientific Collaboration -From the Perspective of 2021 - Olechnicka, Agnieszka; Płoszaj, Adam; Celińska-Janowicz, Dorota (Zagadnienia Naukoznawstwa, 2024)
Two years ago the publication of the monograph The Geography of Scientific Collaboration the authors discuss what issues would have been addressed if the book was written today. Three interrelated matters come up front. The first is the impact of the COVID-19 pandemic on scientific collaboration in both positive and negative ways, also from the geographic perspective. The second is the rise of the virtual conferences with various benefits and challenges they bring, including their inclusively and environmental impacts. The later is the last issue of discussed in the article. The authors identify the environmental effects of academic mobility as one of the key issues that should be addressed by small policies for scientific collaboration in the future.